2019
DOI: 10.29137/umagd.440893
|View full text |Cite
|
Sign up to set email alerts
|

Design of Remotely Controlled Hydraulic Bottle Jack for Automobile Applications

Abstract: Remotely controlled hydraulic bottle jack was designed in this study to alleviate the difficulties encountered during auto servicing that requires certain choice of elevation. Major components of the hydraulic jack were housed in a metal casing of 220mmx220mmx180mm with 2mm thickness. Curb weight (weight of the car with all fluids and components but without the driver, passengers, and cargo) of several cars ranging from 1086kg-1970kg were determined using a scale at nearby automobile shop. Considering the weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Views were automatically generated from the solid model; and dimensions and tolerances were added to the drawing as required. SOLIDWORKS software have been successfully employed in modelling of reciprocating piston [27], remotely controlled hydraulic Bottle Jack [28], vehicle compression springs [29], two stroke internal combustion engine [30], High Density Polyethylene Liner HDPL [31] etc. The wheel was analysed for static and dynamic loads.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Views were automatically generated from the solid model; and dimensions and tolerances were added to the drawing as required. SOLIDWORKS software have been successfully employed in modelling of reciprocating piston [27], remotely controlled hydraulic Bottle Jack [28], vehicle compression springs [29], two stroke internal combustion engine [30], High Density Polyethylene Liner HDPL [31] etc. The wheel was analysed for static and dynamic loads.…”
Section: Methodsmentioning
confidence: 99%
“…This implies that auto wheel material with maximum static nodal stress will fail first before the one with minimum static nodal stress. Considering von-Mises failure theory, material component is said to be in a state of failure if the von-Mises stress exceeds the material yield strength, but if the von-Mises stress value is lower than the material's yield strength, the material is considered to be safe [38,39]. Considering the maximum von-Mises stresses and yield strength obtained from each auto wheel simulated profile, it can be observed that the maximum von-mises stress values for the four (4) wheel materials were below their yield strength, indicating that all the for materials in this study considered are good choice of materials that can withstand the in-service loading condition of an auto wheel application without untimely failure.…”
Section: Magnesium Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…Equation 21 is applicable to rotating parts (21) C r = 1 and C t = 0 However if; (22) C r = 0.56 where Q is the determining factor, C t is either is interpolated or extrapolated for But;…”
Section: (9)mentioning
confidence: 99%
“…Views were automatically generated from the solid model; and dimensions and tolerances were added to the drawing as required. SOLIDWORKS software have been successfully employed in modelling of reciprocating piston [21], remotely controlled hydraulic Bottle Jack [22], vehicle compression springs [23], two stroke internal combustion engine [24], High Density Polyethylene Liner HDPL [25], weld bead penetration on AISI 1020 low carbon steel plate [26] etc. Design drawings of the melon depodding machine were carried out to determine the specific dimension to be selected for each of the machine components.…”
Section: Stainless Steelmentioning
confidence: 99%